2017
DOI: 10.1186/s40580-017-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free perovskite solar cells using Sb and Bi-based A3B2X9 and A3BX6 crystals with normal and inverse cell structures

Abstract: Research of CH3NH3PbI3 perovskite solar cells had significant attention as the candidate of new future energy. Due to the toxicity, however, lead (Pb) free photon harvesting layer should be discovered to replace the present CH3NH3PbI3 perovskite. In place of lead, we have tried antimony (Sb) and bismuth (Bi) with organic and metal monovalent cations (CH3NH3 +, Ag+ and Cu+). Therefore, in this work, lead-free photo-absorber layers of (CH3NH3)3Bi2I9, (CH3NH3)3Sb2I9, (CH3NH3)3SbBiI9, Ag3BiI6, Ag3BiI3(SCN)3 and Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 33 publications
3
54
1
Order By: Relevance
“…The normal (n‐i‐p) structured solar cells show better photovoltaic performance as compared to inverted structures. Baranwal et al have proved it by making a comparison between the normal [n‐i‐p‐Tio 2 ‐perovskite‐Spiro‐OMeTAD) and inverted [p‐i‐n‐NiO‐perovskite‐PCBM) structures . ABX 6 compounds can form perovskite like 3D crystals frameworks like bromoantimonate (V) (N‐EtPY) (SbBr 6 ) with short interhalide contacts .…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…The normal (n‐i‐p) structured solar cells show better photovoltaic performance as compared to inverted structures. Baranwal et al have proved it by making a comparison between the normal [n‐i‐p‐Tio 2 ‐perovskite‐Spiro‐OMeTAD) and inverted [p‐i‐n‐NiO‐perovskite‐PCBM) structures . ABX 6 compounds can form perovskite like 3D crystals frameworks like bromoantimonate (V) (N‐EtPY) (SbBr 6 ) with short interhalide contacts .…”
Section: Lead‐free Perovskitesmentioning
confidence: 99%
“…Regular structure (n-i-p) shows better photovoltaic performance for antimony halide perovskite as compared with the inverted structure (p-i-n). Reference [ 71 ] investigated and compared regular TiO 2 /(CH 3 NH 3 ) 3 Sb 2 I 9 /spiro-OMeTAD) and inverted NiO/(CH 3 NH 3 ) 3 Sb 2 I 9 /PCMB) structures and found that the regular structure performed better with PCE of 0.08%. Chlorine incorporation is a useful tactic to restrain 0-D pattern and stabilize the 2-D phase structure of (CH 3 NH 3 ) 3 Sb 2 Cl x I 9−x .…”
Section: Inorganic Cation Substitutionmentioning
confidence: 99%
“…Therefore, alternative light absorbing materials based on less toxic p ‐block elements such as Sn 2+ , Ge 2+ , Bi 3+ , or Sb 3+ are under intense investigation . Early studies conducted on simply replacing Pb by Bi or Sb in structures like A 3 B 2 I 9 (A=MA, Cs; B=Bi, Sb) were found to result in rather low solar cell efficiencies . The main issue with using trivalent B cations is, that due to charge balance the ABX 3 perovskite structure cannot be maintained.…”
Section: Selection Of Lead‐free Perovskites Reported In Literaturementioning
confidence: 99%